PTEN loss and ERG protein expression are infrequent in prostatic ductal adenocarcinomas and concurrent acinar carcinomas. Issue 14 (14th July 2015) - Morais, Carlos L.; Herawi, Mehsati; Toubaji, Antoun; Albadine, Roula; Hicks, Jessica; Netto, George J.; De Marzo, Angelo M.; Epstein, Jonathan I.; Lotan, Tamara L.
<x xml:space="preserve">Abstract</x> BACKGROUND Prostatic ductal adenocarcinoma is an unusual and aggressive morphologic subtype of prostate cancer. PTEN gene deletion and ERG gene rearrangement are among the most common genomic changes in acinar prostate cancers. Though ductal adenocarcinoma most commonly occurs with synchronous usual‐type acinar adenocarcinoma, little is known about the molecular phenotype of these mixed tumors. METHODS We used genetically validated immunohistochemistry (IHC) assays to assess PTEN and ERG status in a group of 37 surgically treated ductal adenocarcinomas and 18 synchronous acinar adenocarcinomas where we have previously reported ERG gene rearrangement status by fluorescence in situ hybridization (FISH). A group of 34 stage and grade‐matched pure acinar adenocarcinoma cases was studied as a control. RESULTS ERG IHC was highly concordant with ERG FISH results, with 100% (36/36) concordance among ductal adenocarcinomas and 91% (31/34) concordance among 34 pure acinar carcinomas. Similar to previous FISH results, ERG expression by IHC was significantly less common among ductal adenocarcinomas (11% or 4/37) and their synchronous acinar tumors (6% or 1/18) compared to matched pure acinar adenocarcinoma cases (50% or 17/34; P = 0.0005 and 0.002, respectively). PTEN loss by IHC was also less common among ductal adenocarcinomas (18% or 6/34) and their synchronous acinar tumors (22% or 4/18) compared to matched pure acinar carcinomas (50% or 17/34; P = 0.01 and 0.08, respectively). As expected, PTEN loss was enriched among ERG positive compared to ERG‐negative tumors in the pure acinar tumor control group (2.5‐fold enrichment; P = 0.04) however this was not observed among the ductal adenocarcinomas (1.5 fold enrichment; P = NS). Of ductal adenocarcinomas with an evaluable synchronous acinar component, ERG status was concordant in 94% (17/18) and PTEN status was concordant in 94% (16/17). CONCLUSIONS Based on PTEN and ERG, ductal adenocarcinomas and their concurrent acinar carcinomas may be clonally related in some cases and show important molecular differences from pure acinar carcinoma. Prostate 75:1610–1619, 2015. © 2015 Wiley Periodicals, Inc.